Hasil Observasi UMKM Seblak yang Tersebar di Daerah Kabupaten Karawang - Dhea Indri Yanti; Lisna Nadila; Monica Risti Oktaviana; Niken Agustin; Rusmini Icha Indryani; Sartika Sartika; Syifa Aulia Rahman; Miftakul Huda (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
literature, government reports, and other relevant sources. The research results show that seblak MSME entrepreneurs are generally individuals or families with relatively small This research aims to analyze the profile of seblak MSME entrepreneurs, the marketing strategies implemented, the challenges faced, and the contribution of this business to the local economy. This study also aims to identify the key factors that influence the success and sustainability of seblak MSMEs. The research method used is a combination of qualitative and quantitative approaches. Primary data were obtained through in-depth interviews with seblak business owners in several regions and surveys of seblak consumers. Secondary data were collected from related business capital. Effective marketing strategies include the use of social media, product innovation, and word-of-mouth promotion. The main challenges faced are intense competition, fluctuations in raw material prices, and limited access to capital. Nevertheless, seblak MSMEs make a positive contribution to the local economy, especially in creating jobs and increasing community income. The key factors influencing the success of seblak MSMEs include product quality, customer service, business location, and the ability to adapt to market changes. This research suggests the need for support from the government and related parties in the form of training, access to capital, and marketing facilitation to enhance the competitiveness and sustainability of seblak MSMEs. Keywords: MSMEs, consumers, survey, marketing strategy.